Hatch - Oppel, Kenneth, 1967- (Oppel, Kenneth, 1967- Overthrow, 2020)
Fans left desperate for more at the end of Bloom will dive into this second book of the Overthrow trilogy--where the danger mounts and alien creatures begin to hatch. First the rain brought seeds. Seeds that grew into alien plants that burrowed and strangled and fed. Seth, Anaya, and Petra are strangely immune to the plants' toxins and found a way to combat them. But just as they have their first success, the rain begins again. This rain brings eggs. That hatch into insects. Not small insects. Bird-sized mosquitos that carry disease. Borer worms that can eat through the foundation of a house. Boat-sized water striders that carry away their prey. But our heroes aren't able to help this time--they've been locked away in a government lab with other kids who are also immune. What is their secret? Could they be...part alien themselves? Whose side are they on? Kenneth Oppel expertly escalates the threats and ratchets up the tension in this can't-read-it-fast-enough adventure with an alien twist. Readers will be gasping for the next book as soon as they turn the last page...